IN-VITRO FREE-RADICAL SCAVENGING POTENTIAL OF OLIGOPEPTIDES DERIVED FROM WHEAT AND MUNG BEAN - Jha, Suchisree; Ghosal, Mitali; Gupta, Saran Kumar; Ghosh, Amitava; Mandal, Palash (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Therapeutic potential of peptides were well established, but only few information were available on the in vitro antioxidant activities of peptides isolated from wheat and mung bean. Therefore, the aim of this present work is to evaluate the in vitro antioxidant potential of low and high molecular weight oligopeptides separately isolated from one-week old wheat [Triticum aestivum L.] and mung bean [Vigna radiata Wilczek.] seedlings. Methods: Peptides of different molecular weight range were isolated through cryo-crushing followed by solvent partitioning and ion-exchange column and were filtered through the Millipore ultrafiltration system. Purified peptides derived from both samples were assessed for their antioxidant activity. Results: Both ranges of peptides were found to possess significant antioxidant activity. But peptides of low molecular weight (LMW) range (0.5 to 3 kDa) seems to be comparatively more efficient in scavenging free radicals such as DPPH, ABTS+, nitric oxide as well as superoxide than peptides of high molecular weight (HMW), ranging between 3 to 10 kDa. Peptides of LMW from wheat highly responded to metal chelating in comparison to peptides of LMW isolated from mung bean. Conclusion: These peptides may constitute an important part of the antioxidant defense system and could be used for the formulation of Functional foods and Nutraceuticals. Â 